Modulation of immune responses by genetically engineered dendritic cells - Wang, Qi (2013)
Dendritic cells (DCs) are the key players in initiating and guiding innate and adaptive immune responses. In vivo targeting DCs and silencing immune responses via tolerogenic DCs are one of the most promising approaches against a variety of immune-mediated diseases. However many regulatory functions of DCs are still elusive and better understanding of the DC biology would improve the efficacy of the existing and future treatments.